Effect of Maternal Vitamin D Supplementation on Iron Status During Pregnancy. (29th May 2020) - O'Callaghan, Karen; Tariq, Ulaina; Gernand, Alison; Tinajero, Maria; Onoyovwi, Akpevwe; Zlotkin, Stanley; Mahmud, Abdullah Al; Ahmed, Tahmeed; Keya, Farhana; Roth, Daniel
Abstract: Objectives: Vitamin D may have an adjunctive role in the prevention and treatment of iron deficiency (ID) through its proposed role in the regulation of erythropoiesis and circulating hepcidin concentrations. Observational studies have shown associations between low vitamin D and iron status; however, there are few data from intervention trials. In participants of the Maternal Vitamin D for Infant Growth Trial (MDIG; NCT01924013), among whom the baseline prevalence of vitamin D deficiency was 64%, we examined the effect of prenatal vitamin D supplementation on iron status during pregnancy by testing the effect of vitamin D supplementation on serum ferritin concentrations. Methods: In this double-blind, dose-response, randomized trial in Dhaka, Bangladesh, women were recruited at 17–24 weeks' gestation and randomly assigned to receive a prenatal vitamin D3 dose of 4200, 16, 800, 28, 000 IU/week or placebo. Serum ferritin was quantified using an electro-chemiluminescence immunoassay. Plasma C-reactive protein (CRP) was analysed by enzyme-linked immunoassay. Linear regression was used to test the hypothesized effect of vitamin D supplementation on serum ferritin ( n  = 1011 of 1300 enrolled). In a sensitivity analysis, we adjusted for concurrent CRP to correct for inflammation ( n  = 920). Regression correction was used to generate an inflammation-corrected estimate of the prevalence of ID ( n  = 920). Results: Prevalence of ID (serum ferritin <15 µg/L) was high overall (27% corrected for inflammation; 12% uncorrected). Geometric mean (95% confidence interval) serum ferritin concentrations were lower in each of the vitamin D supplementation groups [43.1 (38.1, 48.7), 44.8 (40.4, 49.7) and 45.1 (41.5, 49.1) µg/L in the 4200, 16, 800 and 28, 000 IU/week groups, respectively] compared to the placebo group [50.3 µg/L (45.0, 56.2)], although none of the pairwise differences between each vitamin D group and placebo were statistically significant at the P <   0.05 threshold. Adjusting for CRP did not change the inferences. Conclusions: In a population with concurrently high prevalence rates of iron and vitamin D deficiency, prenatal vitamin D supplementation did not lead to improvements in iron status by late gestation. The possibility of a negative effect of vitamin D supplementation on iron status should be further explored. Funding Sources: The Bill and Melinda Gates Foundation.